The Relationship Between Tendency Towards Entrepreneurship, Marketing Capability, and Firm Performance with the Moderating Role of Competition Intensity in the Field of Information and Communication Technology and Computer Software - Mohammad Mahdi Mozaffari; Mehdi Ajalli; Raheil Garmeei (مطالعات مدیریت کسب و کار هوشمند, 2018)
Several studies conducted over the past few decades on the use of marketing capabilities in manufacturing companies indicate that marketing capabilities are functional and effective and have a positive impact on the corporate level. On the other hand, organizations are increasingly in a position where entrepreneurship is essential for them. Hence, they are increasingly committed to entrepreneurial activities in order to survive and achieve competitive success. The purpose of this study is to identify the impact of entrepreneurial orientation and marketing capabilities on organizational performance, since managers can, by considering these factors, enhance organizational performance and gain benefits such as greater market share and higher profitability. In this regard, after reviewing the related literature, a conceptual model of the relationship between tendency toward entrepreneurship, marketing capability and firm performance with moderating role of competition intensity and research hypotheses is suggested. Validity of the questionnaires was confirmed using formal validity, KMO and Bartlet indicators and Coronbach's alpha coefficient showed the reliability of the questionnaire. The proper R2 values for endogenous structures indicate the adequacy of the model, the appropriate Q2 values indicate the proper predictive power of the model for the exogenous structures and the structural model fitness, and ultimately, the appropriate GOF, indicates the proper power of the model in predicting the variable. To test the hypotheses and the relationship between the variables, PLS (T-value and path coefficients) was used and all the research hypotheses were confirmed.